Decreasing the public health burden of eating disorders: Commentary Schleider et al. (2023). Issue 5 (3rd April 2023) - Fitzsimmons‐Craft, Ellen E.
Abstract: Eating disorders (EDs) are common, disabling, and costly; yet, less than 20% of those with EDs receive treatment. EDs have also skyrocketed in the COVID‐19 pandemic, with access to care worse than ever, further solidifying the need to not only make EDs a priority but also embrace new approaches to address this major public health problem. Schleider et al. argue for the single‐session intervention (SSI) as one such option and outline an agenda that would aid in building the evidence base and realizing the promise of SSIs for EDs. This commentary details three additional key issues that need to be addressed in order to realize the full potential of SSIs and related approaches and ultimately decrease the public health burden of EDs. These include conducting work to optimize interventions for greatest effectiveness, recognizing the value and working to massively increase reach of interventions like SSIs that can scale and meet diverse needs, and engaging in the work needed to address structural barriers to widespread dissemination of these approaches. Through this agenda, we will do more than embrace a single‐session "mindset" and will catalyze the work needed to disseminate SSIs and related approaches at massive scale and maximize their impact.